PROCEEDINGS of the ELEVENTH CANADIAN CONFERENCE ON INFORMATION SCIENCE/COMPTES RENDUS de la ONZIEME CONFERENCE CANADIENNE DES SCIENCES DE L'INFORMATION: COMMUNICATION: "FROM ORGINATOR TO END-USER"/"DU GENERATEUR A L'UTILISATEUR" - Canadian Association for Information Science (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2022)
See PDF